AgriPV Systems: Potential Opportunities for Aotearoa–New Zealand - Donald MacKenzie; Alan Brent; James Hinkley; Daniel Burmester (AgriVoltaics Conference Proceedings, 2024)
The efficient and effective use of land that agriPV, or agrivoltaic, systems offer is especially appealing for Aotearoa-New Zealand, since more than a third of its land area serves agricultural purposes. However, several factors might constrain the implementation of agriPV systems, and different values and preferences need consideration from a community acceptance perspective. As a first step, a high-level investigation into the potential suitability of agriPV systems in Aotearoa–New Zealand was undertaken. The different factors that influence performance of agriPV systems were considered. Then a GIS analysis was undertaken using the analytical hierarchy process – a multicriteria decision-making technique. The spatial data analysis provided insight to identify the regions in Aotearoa–New Zealand best suited to agriPV systems. Overall, it is estimated that 80 percent of the farmland in the country is either good or fairly suitable for agriPV developments with a number of regions identified as potential areas for further investigations.